A Hybrid Method for Solving Traveling Salesman Problem using Hungarian Method - Prasad, AK; Pankaj, (International Journal of Computer Sciences and Engineering, 2025)
Genetic Algorithms are earning respect in different fields of Operation Research like Transportation and Traveling Salesman Problem, etc. However, the best solution they produce needs several iterations to obtain. This paper develops a new hybrid method for Travelling Salesman Problem. The proposed hybrid method delivers same solution each time unlike genetic algorithms. The efficiency is compared against following existing crossover operators; namely, Order Crossover, Modified Order Crossover, Sequential Constructive Crossover, Modified Sequential Constructive Crossover. Experimental results show that the proposed hybrid method is better than the compared methods.